The Effectiveness of the Use of AI (Artificial Intelligence) as a Learning Medium in Arabic Language at Senior High School - Dzilkamala, Kamalina (Study Program of Arabic Language Teaching, 2026)
Arabic language learning at MAN Pekalongan began to integrate Artificial Intelligence (AI) as a supporting medium in the learning process to help deliver material and increase student involvement during learning activities. This study aims to determine the use of Artificial Intelligence (AI) as a learning medium in Arabic language learning and test its influence on the learning effectiveness of grade XI students at MAN Pekalongan. This study uses a quantitative approach with a survey method. The research population consisted of all students of grade XI MAN Pekalongan. The sample was selected using a simple random sampling technique, yielding 68 students from classes XI.1 and XI.3 as respondents. Data were collected through the distribution of questionnaires and analyzed for validity, reliability, classical assumptions, and t-tests to determine the influence of AI use on learning effectiveness. The results of the study indicate that the use of AI in Arabic language learning falls into the good category and has a positive and significant influence on learning effectiveness. The t-test results showed a p-value of 0.000 < 0.05, indicating that AI had a significant effect on student learning effectiveness. Most students also respond positively to the use of AI because it helps them understand the material, increases interest in learning, and provides a more flexible learning experience. These findings suggest that AI can serve as an effective learning medium to support more interactive, flexible, and student-centered Arabic learning.